Cultural competence of maternity care professionals caring for majority population of women with a low socioeconomic position: a scoping review - Maria Dalmaijer; Nadine Emmens; Ank de Jonge; Sanne S. Visser; Esther I. Feijen-de Jong (Discover Public Health)
Abstract Background Although maternity care is linked to improved health outcomes, it is often insufficiently tailored to the needs of low socioeconomic position (SEP) majority population women in high-income countries, leading to obstacles in achieving good health. Cultural competence can contribute to access to adequate care, but no systematic assessment has been conducted. This study aims to examine current evidence about the aspects of cultural competence of maternity care professionals caring for low socioeconomic position (SEP) majority population women. Methods A scoping review was conducted. Search terms were based on the PCC elements (Participants, Concepts, and Context). Data-extraction and analysis were performed by two researchers according to a predetermined procedure. Data were grouped in the main themes of the Seeleman-framework (2009) and subsequently inductively analyzed. Results Out of 6954 articles, 35 were eligible for data analysis. To create an overview of available evidence quality assessment of the included studies was not performed. Health professionals express a lack of knowledge and skills to assess socio-economic vulnerabilities in women and to refer to other care options regarding socio-economic vulnerabilities. Although positive experiences with professionals were mentioned, many women experience negative attitudes in terms of a lack of respect and stigmatization issues. Professionals lack the skills to build good relationships with women. Both women and health professionals reported poor communication and collaboration with health care colleagues and with social services. Conclusions The cultural competence of health professionals in maternity care needs improvement. Professionals should be equipped with sufficient knowledge to identify deprived women and their needs and be trained in skills to effectively communicate and build care relationships. Future research should focus on the reflections of health professionals on their professional role regarding low SEP majority population women. The conditions and maternity care systems health professionals work in to serve low SEP majority women should be studied more closely. Results call for a debate about the scope of professional practice and logistical care structures regarding maternity care for low SEP majority population women. Clinical trial number: Not applicable.